CPW-fed circular-shaped fractal antenna with three iterations for UWB applications - Singhal S.; Pandey A.; Singh A.K. (My University, 2025)
A coplanar waveguide (CPW)-fed circular-shaped fractal antenna with third iterative orthogonal elliptical slot for ultra-wideband applications is presented. The bandwidth is enhanced by using successive iterations of radiating patch, CPW feedline, and tapered ground plane. An impedance bandwidth of 2.9-20.6 GHz is achieved. The designed antenna has omnidirectional radiation patterns along with average peak realized gain of 3.5 dB over the entire frequency range of operation. A good agreement is observed between the simulated and experimental results. This antenna structure has the advantages of miniaturized size and wide bandwidth in comparison to previously reported fractal structures. © 2015 Cambridge University Press and the European Microwave Association.